Intercession of Customer Contentment between Post Sale Services and Repurchase Intention: Evidence from India: Customer Contentment between Post Sale Services and Repurchase Intention (Trinity Journal of Management, IT & Media (TJMITM), 2021)
The concept of post-sale services is getting increased importance in the present marketing environment and considered essential for customer service and contentment. This study tires to examine the impact of post-sale services towards repurchase intention and explores the path followed in this relationship. This study answers the questions – Does post-sale services make the customer agreed and lead to repurchase intention or customer contentment has an independent influence on the relationship between post-sale services and repurchase intention? This was operationalized with the intercession of customer contentment for the relationship between post-sale services and repurchase intention. Data were collected from 222 respondents from India in context of a durable product. The model built up was tested using structural equation modelling. The result shows that customer contentment doesn’t mediate in developing relationship between post-sale services and repurchase intention but to some extent it moderates the relationship. Findings corroborates that marketer should consider customer contentment as a result of post-sale services as necessary up to the minimal required extent and should not over emphasise.
Keywords: Post-sale services; customer contentment; repurchase intention; delivery; installation; intercession